2014
DOI: 10.31901/24566772.2014/08.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Workload on Burnout and Turnover Intention of Medical Staff: A Study

Abstract: There has been a link between nutrition styles and human health and physical features for centuries. Similarly, there has been a connection between the easiness and difficulty to reach food materials, and shortage and abundance of these material and human behaviors and moral structure. One of the efforts to make a connection between these qualifications comes from Ibn Khaldun. A thinker of Islam, Ibn Khaldun, who lived in the 18 th century, stated that moral characteristics and physical features in the communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 10 publications
2
49
0
10
Order By: Relevance
“…Burnout is related to job cognitive demands, including workload, and to temporal and emotional demands, such that workers who perceive a high level of workload will have a greater risk of suffering job burnout and exhaustion at work. Several studies show this relationship [13][14][15].…”
Section: Job Demands Individual Resources and Burnoutmentioning
confidence: 86%
“…Burnout is related to job cognitive demands, including workload, and to temporal and emotional demands, such that workers who perceive a high level of workload will have a greater risk of suffering job burnout and exhaustion at work. Several studies show this relationship [13][14][15].…”
Section: Job Demands Individual Resources and Burnoutmentioning
confidence: 86%
“…et al, (2019), state that workloads have a very strong and direct relationship with the employee's intention to leave, which means that if the workload gets higher then the employee's desire to leave will also increase. Xiaoming et al, (2014); Santosa et al, (2017), in his research stated that there is a positive effect of workload on employees' intention to leave. Qureshi et al, (2013), found that there was a positive relationship between workload and intention to leave employees.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Employee workload has also been defined as the perceived relationship between the amount of mental processing capability or resources required to complete a task (Hart and Staveland, 1998). Empirical studies indicate that employee workload impact on emotional commitment (Erat et-al, 2017) exhaustion (Ali S and Farooqi, 2014;Portoghese et al, 2014); individual and organisational stress (Erat et al, 2017;Rahim et al, 2016;;Hombergh et al, 2009; as well as Xiaoming et al, 2014) employee performance and job satisfaction (Herminingsih and Kurniasih, 2018;Liu and Lo, 2018;Akobo, 2016;Rahim et al, 2016;Ali S and Farooqi, 2014;as well as Hombergh et al, 2009), and turnover intention (Qureshi et al, 2013).…”
Section: Concept Of Employee Workloadmentioning
confidence: 99%